DOES CURRENT PRE-HOSPITAL CARE FOR PATIENTS AT THE END OF THEIR LIFE REFLECT BEST PRACTICE GUIDANCE?. Issue 6 (19th May 2015) - Shaw, Joanna; Fothergill, Rachael; Murphy-Jones, Georgina
Abstract : Introduction: The end of life care good practice guide encourages organisations to enable terminally ill patients to be cared for and die outside of hospital. Ambulance services play a critical role in achieving this goal, however little guidance exists for ambulance crews. Method: To determine the current levels of care provided, a retrospective review was conducted of 50 end of life care records. Findings were communicated to staff with a questionnaire to determine levels of confidence caring for these patients (61 responded); prior to a prospective review of a further 30 records. Results: Only 4% of patients had out-of-hours information registered with the ambulance service. 48% were attended out-of-hours and their wishes were unknown. 38% of crews consulted with the patients' GP/palliative care team to determine whether the patient had a plan for their end of life. 88% of patients were conveyed (27% to a hospice and 73% to A&E). 53% of survey respondents were not confident treating this patient group. Respondents identified training needs, specifically on: alternative care pathways, evidence of terminal illness and DNA-CPR orders. Pain and discomfort was considered for 83% of patients, with subsequent action taken for 73%. Patients' wishes were not documented for 79%, however the patient's diagnosis and prognosis was clear for 97%. Referrals to A&E, a hospice or to the patient's GP/palliative care team were felt to be appropriate to the patient's presenting complaint for 93%. Conclusion: Crews are not able to access out-of-hours information for end of life patients and are therefore not always aware of the patient's wishes. The care provided to the majority of patients was good, but the questionnaire showed most respondents were not sufficiently confident when treating end of life patients. Further work is needed to ensure crews are able to determine patients' wishes and training could increase confidence treating this patient group.